2006
DOI: 10.1016/j.pec.2005.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Does stimulating self-care increase self-care behaviour for minor illnesses of Dutch and Turkish inhabitants of a deprived area in The Netherlands?

Abstract: In developing future healthcare-reducing interventions, one should be aware of possible unwanted side effects in non-western populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Some articles reported different aspects of the same study or data set: Plass et al, 75,76 Rutten et al, 77,78 and Hibberd et al 79 and Wagner et al 80 There were 64 studies in total. Other articles were written by the same author, testing the same intervention in different ways on different populations, [81][82][83] with Herman and Mayer 82 undertaken as a pilot for Herman and Jackson.…”
Section: Articles Reporting the Same Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Some articles reported different aspects of the same study or data set: Plass et al, 75,76 Rutten et al, 77,78 and Hibberd et al 79 and Wagner et al 80 There were 64 studies in total. Other articles were written by the same author, testing the same intervention in different ways on different populations, [81][82][83] with Herman and Mayer 82 undertaken as a pilot for Herman and Jackson.…”
Section: Articles Reporting the Same Studymentioning
confidence: 99%
“…[108][109][110][111][112] Many such interventions reported the corollary rationale of reducing unnecessary primary or emergency care use as a result of improved knowledge. 53,75,76,103,113,114 Unlike the primary and emergency care interventions, the majority of community and workplace-based interventions had the specific aim of improving self-care and participants' knowledge, both of illnesses (including some specific minor problems such as childhood fever or cough) [79][80][81][82][115][116][117][118][119][120][121] and when to access what service. 122,123 A smaller number of such studies explicitly reported that the aim of an intervention was to reduce use of primary care, 124 emergency care 125,126 or health services generally.…”
Section: Rationale For the Interventionmentioning
confidence: 99%
See 3 more Smart Citations